Empowering choices: a review of family planning and contraceptives - Abdul Rashid, Nor'ain; Muhammad Rafi Ravi, Jezreen Syaza; Othman, Hamidah; Jamil, Nurul Akma; Muhammed, Auwalu (Qualitative Research Association of Malaysia, 2025)
Family planning is crucial and offers benefits for individuals, families, and society. The use of contraceptive methods is key to promoting good health, addressing population growth, and meeting reproductive health needs. Sociodemographic factors often influence knowledge and practices surrounding family planning. This article reviews previous studies on women's family planning and contraceptive use, discussing knowledge, attitudes, and behaviours, and evaluating the relationship between sociodemographic factors. It integrates findings from previous research and highlights issues. The online search for nursing and medical journals published between 2018 and 2023, as well as the library databases, was accessed through electronic databases. The studies were critically appraised using the JBI Critical Appraisal Tool for Analytical Cross-Sectional Studies. The studies included were critically appraised for quality. There were 40 studies in this review. The findings were synthesized by organizing the studies based on common themes, objectives, and patterns. Four main themes emerged regarding family planning and contraception: Knowledge, Attitude, Practice, and the relationship between sociodemographic characteristics and knowledge, attitude, and practice. The review concludes by emphasizing the importance of understanding the sociodemographic factors influencing family planning and contraceptive use. Numerous factors, such as financial situation, age, occupation, ethnicity, religion, and level of education, all have a significant impact on this issue. Therefore, healthcare professionals and policymakers must collaborate to develop interventions that raise public awareness and promote positive changes, ultimately leading to better outcomes for women and society. This review serves as a vital foundation for developing culturally appropriate, evidence-based therapies.